To solve the equation \( 13x + 26 = 3x - 34 \), we can follow these steps:
- First, let's get all the \( x \) terms on one side and the constant terms on the other side. We can start by subtracting \( 3x \) from both sides:
\[ 13x - 3x + 26 = -34 \]
This simplifies to:
\[ 10x + 26 = -34 \]
- Next, we need to isolate the term with \( x \). We can do this by subtracting \( 26 \) from both sides:
\[ 10x = -34 - 26 \]
This simplifies to:
\[ 10x = -60 \]
- Now, to solve for \( x \), we divide both sides by \( 10 \):
\[ x = \frac{-60}{10} = -6 \]
Thus, the solution is:
\[ x = -6 \]
So the correct response is x equals negative 6.